Cost-effectiveness and reliability evaluation of hydrogen storage-based hybrid energy systems for unreliable grid - Irham A.; Hannan M.A.; Rahman S.A.; Ker P.J.; Wong R.T.; Roslan M.F.; Begum R.A.; Jang G. (Elsevier Ltd, 2025)
A critical issue regarding the unreliable electricity supply in regions experiencing frequent grid outages poses significant economic and social challenges. Despite the integration of renewable energy sources like photovoltaic (PV) systems, the intermittent nature and low reliability of these resources necessitate additional energy storage solutions. The study investigates the effectiveness of various power system configurations, including PV only, PV/BES, and PV/BES/H2 systems. Using HOMER software, the study delves into investigating the impact of different outage parameters, specifically focusing on the outage durations and frequencies to the reliability and cost-effectiveness of these systems. The study analyzes how these outage parameters influence the loss of power supply probability (LPSP) and the cost of energy (COE). Three cases were being investigated in this study, which are Case 1: Varying mean outage duration (MOD) with fixed outage frequency (OF), Case 2: Varying OF with MOD and Case 3: Varying both the MOD and OF. The inclusion of H2 storage significantly reduced the LPSP in Case 1, from a range of 0.882%?2.79% in the PV/BES system to a much lower range of 0.15%?0.392%. In Case 2, the PV/BES/H2 system also markedly improved reliability, lowering the LPSP from 0.0751% to 1.28% in the PV/BES system to just 0.0279%?0.189%. The results of Case 3 demonstrate that OF has a greater impact on system reliability, as evidenced by a significantly larger rate of change in LPSP when varying OF with constant MOD compared to varying MOD with constant OF. Therefore, the inclusion of energy storage significantly enhances reliability, with the PV/BES/H2 system showing the lowest LPSP values in both cases. However, COE for the PV/BES/H2 system was higher in both cases, ranging from 0.22 to 0.326 $/kWh, compared to 0.101 to 0.156 $/kWh for the PV/BES system. This highlights the need for advancements in H2 storage technology to reduce cost. These findings underscore the critical importance of accurately sizing components to ensure a reliable and economical power supply in regions with unstable grids. ? 2024 Hydrogen Energy Publications LLC